Pengaruh Turbo Marketing Dan Viral Marketing Terhadap Keputusan Pembelian Pada Pengguna Tiktok Shop Di Kota Bima - hanandita, Putri Mutiara; Sri Ernawati (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2024)
This research aims to determine Turbo Marketing and Viral Marketing among Tiktok Shop users in Bima City. The type of research used is associative, research location in Bima City. The population in this study were all consumers who had purchased at the Tiktok Shop. The sample in this study was 50 people using a purposive sampling technique. The research instrument uses a questionnaire with Likert scale measurements. The type of data used in this research is quantitative data with the research data source being primary data. Data collection techniques are observation, questionnaires/questionnaires and literature study. Data analysis uses validity test, reliability test, classical assumption test, multiple linear regression test, determination test, correlation test, t test and F test. The results of the study state that Turbo Marketing has no significant effect on Purchasing Decisions, Viral Marketing has a significant effect on Purchasing Decisions Purchases as well as Turbo Marketing and Viral Marketing together have a significant influence on Purchase Decisions to Purchase at the Tiktok Shop in the city of Bima